The electronic properties of boron-doped germanium nanocrystals films - Dan Shan; Menglong Wang; Daoyuan Sun; Yunqing Cao (Discover Nano, 2023)
Abstract Various doping concentrations of boron (B)-doped germanium nanocrystal (Ge NC) films were prepared using the plasma-enhanced chemical vapor deposition (PECVD) technique followed by thermal annealing treatment. The electronic properties of B-doped Ge NCs films combined with the microstructural characterization were investigated. It is worthwhile mentioning that the Hall mobilities $${μ }_{Hall}$$ μ Hall of Ge NCs films were enhanced after B doping and reached to the maximum of 200 cm2 V−1, which could be ascribed to the reduction in surface defects states in the B-doped films. It is also important to highlight that the temperature-dependent mobilities $${μ }_{H}(T)$$ μ H ( T ) exhibited different temperature dependence trends in the Ge NCs films before and after B doping. A comprehensive investigation was conducted to examine the distinct carrier transport properties in B-doped Ge NC films, and a detailed discussion was presented, focusing on the scattering mechanisms involved in the transport process.